Green Technology for Sustainable Disaster Management and Recovery - Shivmuni, Pooja (Journal of Advanced Research in Alternative Energy, Environment and Ecology; Vol 11 No 1&2 (2024): Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2024)
Natural catastrophes are becoming more frequent and intense, endangering populations throughout the world and necessitating creative and long-lasting approaches to disaster relief and recovery. The integration of green technologies is examined in this review paper as a cogent strategy to address these issues. The primary goals are to evaluate the state of disaster management procedures as they exist today, examine the possibilities of green technology, and provide a structure for integrating them. This review paper’s methodologies include a thorough examination of the body of research, case studies, and instances of effective green technology applications in crisis management. Highlighting the beneficial effects of green technologies on mitigating environmental degradation, boosting resilience, and guaranteeing a more sustainable recovery process, the study summarises its main conclusions. Reducing the environmental impact of disaster response operations is largely dependent on the use of green technology, which includes enhanced monitoring systems, renewable energy sources, and environmentally friendly building materials. This paper promotes the use of green technology integration as a pillar of environmentally friendly disaster relief and management.